Chromosome end protection by blunt-ended telomeres - Kazda, Anita (Cold Spring Harbor Laboratory Press, 2012)
Single-stranded telomeric DNA protrusions are considered to be evolutionarily conserved structural elements essential for chromosome end protection. Their formation at telomeres replicated by the leading strand mechanism is thought to involve poorly understood post-replicative processing of blunt ends. Unexpectedly, we found that angiosperm plants contain blunt-ended and short (1- to 3-nucleotide) G-overhang-containing telomeres that are stably retained in post-mitotic tissues, revealing a novel mechanism of chromosome end protection. The integrity of blunt-ended telomeres depends on the Ku70/80 heterodimer but not on another telomere capping protein, STN1. Curiously, Ku-depleted telomeres are fully functional. They are resected by exonuclease 1, promoting intrachromatid recombination, which may facilitate formation of an alternative capping structure. These data challenge the view that telomeres require ssDNA protrusions for forming a functional capping structure and demonstrate flexibility in solutions to the chromosome end protection problem.